Bright soliton of Stochastic perturbed Biswas-Milovic equation with cubic-quintic-septic law having multiplicative white noise - Ozdemir, N.; Altun, S.; Ozisik, M.; Secer, A.; Bayram, M. (SOC MEXICANA FISICA, 2024)
For the first time, the adopted stochastic form of the perturbed Biswas-Milovic equation with cubic-quintic-septic law having spatio-temporal and chromatic dispersion in the presence of multiplicative white noise in Itosense was presented and examined. The Biswas-Milovic equation models numerous physical phenomena occurring in optical fiber. We analyzed the optical soliton solutions of the stochastic model with the aid of a subversion of the new extended auxiliary equation method. Furthermore, we investigated the evaluation of the noise impacts and the effects of some model parameters on the dynamics of the generated soliton. Finally, graphical depictions of the derived soliton types were represented for some solution functions. The stochastic model and the derived results will contribute to the comprehension of the nonlinear dynamics of pulse propagation in optical fibers which has great importance for the advancement of optical communication engineering.
Keywords: Stochastic model; Wiener process; Noise strength; Brownian motion; PORSEZIAN-DANIEL MODEL; OPTICAL SOLITONS; Physics